First molecular identification of two Leptospira species (Leptospira interrogans and Leptospira wolffii) in Bangladesh. (September 2019) - Aziz, M.A.; Aung, M.S.; Paul, S.K.; Ahmed, S.; Haque, N.; Roy, S.; Al Amin, M.; Paul, A.; Miah, M.A.H.; Alam, M.K.; Islam, M.S.; Hossain, M.A.; et al.
Abstract: Leptospiral 16S rRNA genes were detected in 13 blood samples from 74 febrile patients in north-central Bangladesh, and their sequences phylogenetically clustered with those of Leptospira interrogans or Leptospira wolffii . Genetic diversity in O-antigen polymerase ( wzy ) was found in an L. interrogans sample.